Toucher avec les mots: ordalie et épidictique - Mazzeo, Marco (Rivista Italiana di Filosofia del Linguaggio, 1970)
In the rhetorical tradition the epideictic is considered a minor and unremarkable genre. On the other hand, the ordeal is usually considered as a barbaric institution to be expunged from Western institutional systems. The analysis of this unusual couple, made of a neglected rhetorical praxis and an institution which is usually seen as menacing, could offer new ideas about the relation between language, institutions and human nature. In this respect, the essay proposes a clear hypothesis : the relation between epideictic rhetoric and ordeal is specular and complementary.